Review of the Surgical Approaches for Peyronie's Disease: Corporeal Plication and Plaque Incision with Grafting - Viet Q. Tran; Dennis H. Kim; Timothy F. Lesser; Sherif R. Aboseif (Advances in Urology)
The understanding and management of Peyronie's disease (PD) has improved but elucidating the exact etiology of the disease has yet to be achieved. In this paper, we review the historical and clinical aspects of PD. We focus on the evolution of surgical management for PD and review recent published articles that compare popular surgical techniques such as plication and plaque incision with vein graft. These two techniques have been reported to be equivalent with respect to patient satisfaction; however, each technique has its own advantages and disadvantages.